Production of bacteriocin-like agents of Budvicia aquatica and "Pragia fontium" - Smarda, J (Zentralblatt fur Bakteriologie, Mikrobiologie, und Hygiene. Series A, Medical microbiology, infectious diseases, virology, parasitology, 1987)
In cultures of 9 budvicia aquatica and 5 "Pragia fontium" strains production of distinct bacteriocin-like agents was proved. It is suggested to call them aquaticins and fonticins. They display strain specific antibacterial activities towards both genera; however, they are not active towards Escherichia coli or Shigella sonnei indicators. Their inhibition zones are conspicuously narrow (turbid or clear). Their spontaneous production may be enhanced by UV-induction of producing bacteria. They are readily set free into the medium; no intracellular accumulation occurs. With only one exception, they are trypsin-resistant and remarkably heat-sensitive, being damaged at 45 degrees C to 55 degrees C. All these results suggest that aquaticins and fonticins are of corpuscular character. This assumption was proved true by electron microscopic observation of one of the fonticins: this resembles contracted tails of bacteriophage T4.
Keywords: Trypsin; kultivační média; Ultraviolet Rays; elektronová mikroskopie; trypsin; Microscopy, Electron; Hot Temperature; Bacteriocins; vysoká teplota; ultrafialové záření; Enterobacteriaceae; Culture Media; bakteriociny